Analysis of clean water demand at the Kutaraja Fishing Port (PPS Kutaraja) Lampulo Banda Aceh - Iwan Musawir; Makwiyah A Chaliluddin; Muhammad Rusdi; Aprianty Aprianty (Depik Jurnal)
The Kutaraja Fishing Port (PPS Kutaraja) serves as a central hub for the fisheries sector in Aceh Province. Clean water is one of the essential facilities that plays a vital role in supporting port activities. If issues related to clean water supply are not addressed, they are predicted to affect fish quality, reduce user confidence in PPS services, and hinder operations at the port.This study aims to determine the level of clean water demand at PPS Kutaraja, Lampulo, Banda Aceh. The research was conducted from October to November 2024. The method used was a survey approach with purposive sampling techniques. Data analysis employed a quantitative descriptive method by calculating the total clean water demand, which includes clean water needs for fishing activities at sea, for ice factories, and for office use. The results of the analysis showed that the total clean water demand  at PPS Kutaraja is 163,522 liters/day, clean water demand for fishing activity is 18,142 liters/day, ice plant requirement is 144,000 liters/day, and office use is 1,380 liters/day. Based on interviews and field observations, fishermen individualy need to purchase clean water from tank trucks agents. Therefore, a strategic policy is needed for clean water management at PPS Kutaraja.